Relevant, applicable learning and research - Daing Nasir, Ibrahim (2013)
Since inception, UMP has positioned itself as a hands-on technical university emphasising competency in engineering and technology without compromising the knowledge component in the teaching and learning process. To that extant, UMP has introduced the 'Teaching Factory' (TF) approach in three of its engineering faculties - mechanical, chemical and manufacturing - in teaching delivery.